2022
DOI: 10.3390/horticulturae8030199
|View full text |Cite
|
Sign up to set email alerts
|

Pomological Traits and Genome Size of Prunus armeniaca L. Considering to Geographical Origin

Abstract: Apricot (Prunus armeniaca L.) is an important fruit crop and member of the Prunus genus of the Rosaceae family that is planted in many temperate regions worldwide. The quality of fruit is assessed by many pomological parameters which can serve as a decisive factor in apricot breeding, because the introduction of new cultivars is required. These parameters can differ with climate conditions, geographical location or geographic ecological origin. Similarly, another biological characteristic can be measured depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In this instance, differences in TSS are primarily due to the genetic background of apricot cultivars and, to a lesser extent, the maturity stage. The content of TSS in selected apricot cultivars is substantially lower than that reported by Cirillo et al [31] for apricot cultivars grown under Southern conditions and consistent with those of Rampáčková et al [32] reported for apricot cultivars originating from Central Europe, Central Asia, and the USA. Analyzing the TSS of developed DCF products, a statistically higher (p < 0.05) amount was found in cv.…”
Section: Physical-chemical Characteristics Of Apricot Fruit and Its C...supporting
confidence: 89%
“…In this instance, differences in TSS are primarily due to the genetic background of apricot cultivars and, to a lesser extent, the maturity stage. The content of TSS in selected apricot cultivars is substantially lower than that reported by Cirillo et al [31] for apricot cultivars grown under Southern conditions and consistent with those of Rampáčková et al [32] reported for apricot cultivars originating from Central Europe, Central Asia, and the USA. Analyzing the TSS of developed DCF products, a statistically higher (p < 0.05) amount was found in cv.…”
Section: Physical-chemical Characteristics Of Apricot Fruit and Its C...supporting
confidence: 89%
“…Apricot is particularly suitable for low-input growing agricultural systems as observed in southern Italy, where organic apricot production is spreading widely [2]. The total world production is approximately 2.6 million tons, with Uzbekistan and Turkey as the leading countries in the production of fresh apricot fruits (www.fao.org/faostat/en/#data/QC accessed on 10 November 2021) [3]. Italy is the fifth worldwide and the first European producer of apricots, with 222.690 tons (www.fao.org/faostat/en/#data/QC accessed on 10 November 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors can also affect plant phenotypes. For example, trait differences among populations in different geographical environments have been detected in Olea europaea [19], Phoenix canariensis [20], and Prunus armeniaca [21]. Previous studies have shown that nutrient stress has a significant effect on the macroscopic characteristics of Arabidopsis [22].…”
Section: Introductionmentioning
confidence: 99%